Potential For Ecotourism Development In Jambi Province - Citra Sherly Gita; M. Yudhi Pangestu; Ümit Atabek (LPPM Universitas PGRI Sumatera Barat, 2023)
Jambi Province in Indonesia is a province that has rich natural resources and cultural diversity. The potential of an area can have a big influence as a tourist destination. Potential and superior objects that tourists can see in Jambi Province include the natural beauty of the area, such as the sea, hills and mountains, as well as local culture. This research was carried out with the aim of future ecotourism activities in Jambi Province, especially Kerinci Seblat National Park (TNKS), Bukit Tigapuluh National Park (TNBT), Bukit Duabelas National Park (TNBD), and Berbak and Sembilang National Park (TNBS). . This National Park is suitable for commercial use and standard tourist attractions. The social theory used in this research is Herbert Spencer's theory. In Spencer's view, sociology is a science that observes social structures and processes as a system. The type of research method used is qualitative through a descriptive approach. The research results show that the ability to develop tourism in this area consists of the coverage of the regional ecosystem which is created from a natural combination of hilly forests, rivers (bengawan), sea, wildlife, and most importantly protected. valuable plant species, such as germplasm. The conclusion of this research is that the classes that fall into the very rare and protected category and do not have visual appeal are tropical forest medicinal biota as well as conventional insight and local customs. The novelty of this research is the most important species that are protected, valuable flora such as germplasm, species that are classified as very rare and protected and do not have visual appeal, tropical forest medicinal biota as well as conventional insights and local community customs.